Thermal Performance of Waste Rubber Wall Panel (WRWP) as Overheat Resistance in Building Construction - An Nisha Nur Welliana Abd Rased; Saleh, Alia Abdullah; Samsul Rijal, Nurhidayah binti (International Journal of Sustainable Construction Engineering and Technology, 2022)
One of the significant Malaysian building development issues would be overheating building space as the common building materials are unable to control thermal absorption in the building. Based on Malaysia Standard Department 2007 guideline, the recommended temperature for interior design environment in Malaysia should be between 23ºC and 26ºC. Because of its area located at latitude 4.2105° N and longitude 101.9758° E, Malaysia gets the sun almost every day throughout the year. A significant heat increase in Malaysian houses gets from building elements. Therefore, this situation is because the common building material cannot control the thermal absorbent into the building. Laboratory analysis was conducted to determine the feasibility of developing a low-cost building material with acceptable thermal properties. The thermal performance of the used waste rubber was investigated to produce the new insulation building material (WRWP). Waste rubber from tyre production was used in this study. 700 grams of waste rubber was mixed with 400 grams of adhesive glue for every wall panel. Installing WRWP helps to decrease 28% of indoor temperature compared to buildings without WRWP. It also helps to slow down the heat increase when the temperature outside the building increases. WRWP installation also accelerated internal temperature when the temperature outside decreases.